Cloud nine : a novel - Rice, Luanne (Bantam Books, 1999)
Sarah Talbot has beaten the cancer and reopened her bedding boutique, Cloud Nine. In celebration, Sarah's friends give her a special present: a ride over her upstate New York town in a chartered plane. It is on this flight that Sarah meets Will Burke, a former Navy pilot whose outward confidence hides the wounds he has yet to heal.